2005
DOI: 10.1021/es048287d
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of 243Am(III) to Multiwall Carbon Nanotubes

Abstract: Carbon nanotubes have attracted great interest in multidisciplinary study since their discovery. Herein, radionuclide 243Am(III) sorption to uncapped multiwall carbon nanotubes (MWCNTs) was carried out at 20+/-2 degrees C in 0.01 and 0.1 M NaClO4 solutions. Effects of 243Am(III) solution concentration, ionic strength, and pH on 243Am(III) sorption to MWCNTs were also investigated. The sorption is strongly dependent on pH values and weakly dependent on the ionic strength in the experimental conditions. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(190 citation statements)
references
References 29 publications
5
185
0
Order By: Relevance
“…The as-grown MWCNTs (raw MWCNTs) were used directly in the experiments. Part of the samples was added into the solution of 3M HNO 3 to remove the hemispherical caps of the nanotubes [16]. Thus oxidized MWCNTs were also studied as a comparison.…”
Section: Experimentation Adsorption Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The as-grown MWCNTs (raw MWCNTs) were used directly in the experiments. Part of the samples was added into the solution of 3M HNO 3 to remove the hemispherical caps of the nanotubes [16]. Thus oxidized MWCNTs were also studied as a comparison.…”
Section: Experimentation Adsorption Materialsmentioning
confidence: 99%
“…Li et al [27] had ever measured the point of zero charge (pH pzc ) of oxidized MWCNTs and found it to be about 5. We measured the pH pzc of oxidized MWCNTs to be ~5 in our previous paper [16].…”
Section: According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and his colleagues performed a series of experimental investigations on nuclear waste treatment and disposal [27][28][29]. One of their research areas is to explore the potential applications of multi-wall carbon nanotubes (MWCNTs) to treat nuclear waste.…”
Section: Environmental Radiochemistrymentioning
confidence: 99%
“…Carbon nanotubes have attracted great interest in multidisciplinary study since their discovery. Wang et al studied the 243 Am(III) sorption to uncapped MWCNTs in NaClO 4 solutions, and found that MWCNTs can adsorb 243 Am(III) with extraordinarily high efficiency by forming very stable complexes, where chemisorption or chemicomplexation is the main mechanism [28]. Their investigations indicated that MWCNTs might be a promising candidate for the preconcentration and solidification of 243 Am(III) or its analogue lanthanides and actinides from large volumes of aqueous solution.…”
Section: Environmental Radiochemistrymentioning
confidence: 99%